The preferability of internal fixation in comparison to external fixation in geriatric patients after distal radial fracture in terms of functional and clinical outcomes – a systematic review - Kupniewski, Kuba; Krawczyk, Kornelia; Majka, Karolina; Perenc, Helena; Pasieka, Karolina; Korzonek, Urszula; Kosiorowska, Paulina; Kosar, Michał; Pędras, Marek (Quality in Sport, 2024)
Background: Distal radial fractures (DRFs) are common in the elderly, particularly among those over 65, due to factors such as osteoporosis, falls, and comorbidities. Treatment options, including external fixation (ExFix) and internal fixation (IF) with volar locking plates (VLPs), offer different benefits and drawbacks, making the optimal approach for elderly patients a topic of ongoing debate. Objective: This systematic review aims to evaluate the effectiveness and safety of different treatment modalities for DRFs in elderly patients, focusing on functional outcomes, radiographic parameters, and complication rates. Methods: A comprehensive search was conducted on PubMed, focusing on studies comparing ExFix and IF in elderly patients. Studies were screened based on predefined inclusion criteria, and data on functional outcomes, radiographic alignment, and complications were extracted and analyzed. Results: Two studies met the inclusion criteria. Huang et al. demonstrated that VLPs offered better functional outcomes, with improved supination and fewer complications, compared to ExFix. In contrast, the systematic review by Diaz-Garcia et al. suggested that while VLPs generally provided good outcomes, Non-Bridging External Fixation (Non-BrEF) showed superior grip strength in some analyses. Radiographic outcomes varied, with VLPs typically providing better volar tilt and radial inclination, though the clinical significance of these differences remains uncertain. Complication rates were lower with VLPs in Huang et al.'s study, but Diaz-Garcia et al. noted a higher incidence of major complications requiring surgery with VLPs. Conclusion: The findings suggest that VLPs may offer superior functional outcomes and lower complication rates compared to ExFix in elderly patients with DRFs. However, further research is needed to clarify the clinical significance of these differences and optimize treatment strategies for this vulnerable population.